Nitroglycerin for Management of Retained Placenta: A Multicenter Study - Maria Bullarbo; Hans Bokström; Håkan Lilja; Elisabeth Almström; Nina Lassenius; Agneta Hansson; Erling Ekerhovd (Obstetrics and Gynecology International)
The primary aim was to determine if sequential administration of oxytocin and nitroglycerin is effective for management of retained placenta when performed by obstetricians with no experience of the method. Secondary aims were to examine possible adverse effects of nitroglycerin. One hundred and five women with retained placenta were randomly selected to receive either 1 mg nitroglycerin or placebo tablets sublingually if intravenous oxytocin had failed to expel the placenta. At two of the hospitals some of the midwives were familiar with the use of nitroglycerin. The other midwives and all the participating obstetricians had no clinical experience of the method. In the treatment group, detachment of placenta following nitroglycerin occurred in 37.3% of the women compared to 20.4% in the placebo group (P=0.056). In the two hospitals with some experience of the method, placenta was removed in 9 of 19 (47.4%) women in the nitroglycerin group compared to 3 of 17 (15.0%) women in the placebo group. No adverse effects of clinical importance were registered. Although the difference between the two groups did not reach statistical significance, the higher success rate in the two hospitals with some experience could indicate that clinical experience is of importance in order to achieve placental detachment.